CHALLENGES AND OPPORTUNITIES FOR LITERACY AND TECHNOLOGY IN ENGLISH LANGUAGE TEACHING - Dwiana Novitasari; Umniyati Ris’ah; Dwi Astuti Wahyu Nurhayati (Jurnal Bahasa Lingua Scientia, 2025)
This study aims to analyze the challenges and opportunities in integrating literacy and technology in English Language Teaching (ELT) among English teachers within the English Teachers’ Community (MGMP Bahasa Inggris) in Trenggalek. The main objective is to investigate teachers' perspectives on literacy and its integration with digital tools in ELT. This review includes studies focused on literacy and technology integration in English education, particularly those involving teacher experiences in classroom settings, while excluding research unrelated to technology use or ELT practices. Sources were gathered from ERIC, Google Scholar, and Scopus, with the final search conducted in October 2024. A descriptive qualitative approach was employed to gain an in-depth understanding of the issue. The risk of bias was assessed using methodological quality indicators and participant selection criteria. Thematic synthesis was used to analyze results across studies. The findings reveal that traditional literacy approaches—emphasizing reading and writing—remain dominant; however, there is growing recognition of the need to broaden literacy to include speaking, listening, problem-solving, and digital proficiency. Teachers reported using digital tools such as Google Classroom, Edmodo, Google Forms, WhatsApp, Duolingo, and various AI-based applications to support instruction. These tools present both challenges and opportunities. Challenges include concerns about declining writing skills due to digital communication habits and the complexity of integrating technology effectively into literacy instruction. Opportunities arise from technology’s potential to enhance student engagement, creativity, and expression by offering diverse methods for demonstrating understanding. The study concludes that literacy education must adapt to technological advancements, and educators need flexible strategies to foster comprehensive literacy skills aligned with contemporary demands. This adaptation requires ongoing professional development and supportive systems to ensure effective technology integration in ELT.